Tactical positioning in short-track speed skating: The utility of race-specific athlete-opponent interactions. Issue 5 (4th May 2023) - Hext, Andrew; Hettinga, Florentina Johanna; McInerney, Ciarán
ABSTRACT: In short-track speed skating, tactical positioning is essential for success as the race format (head-to-head) prioritises finishing position over finishing time. At present, our understanding of this phenomenon is based on measuring the similarity between athletes' intermediate and final rankings. However, as this approach groups athlete performances across races, each lap's estimate of tactical importance ignores the athlete-opponent interactions specific to each race. Here, we examine the utility of race-specific athlete-opponent interactions for investigating tactical positioning. Using intermediate and final rankings of elite 1, 000 m short-track speed skating competitors collected from 2010/11–2017/18 (n = 6, 196, races = 1, 549), we compared the current method to a novel approach that accounted for race-specific athlete-opponent interactions. This approach first applied the current method to each race independently before using these values to form (1) discrete, empirical distributions of each lap's tactical importance and (2) race-specific tactical positioning sequences. Our results showed that accounting for race-specific athlete-opponent interactions provided a higher measurement granularity (i.e. level of detail) for investigating tactical positioning in short-track speed skating, which better captured the complexity of the phenomenon. We observed 61 different tactical positioning behaviours and 1, 269 unique tactical positioning sequences compared to the current approach's nine-point estimates of tactical positioning importance. For this reason, we recommend that researchers and practitioners account for race-specific athlete-opponent interactions in the future as it offers a deeper understanding of tactical positioning that will enhance both strategic and tactical decisions. Highlights We compare the current approach for investigating tactical positioning to a novel approach that accounts for race-specific athlete-opponent interactions. We show that accounting for race-specific athlete-opponent interactions provides a higher measurement granularity (i.e. level of detail) for investigating tactical positioning in short-track speed skating. We demonstrate that this increased measurement granularity can facilitate a deeper understanding of tactical positioning by (1) producing theoretically-more-correct point estimates of tactical positioning importance, (2) enabling more rigorous statistical analyses into the effect of athlete-environment interactions on tactical positioning behaviour, and (3) allowing sequential analyses that capture the progressive relationships between laps. We recommend that researchers and practitioners account for race-specific athlete-opponent interactions in future investigations, as the findings will enhance analyst, coach, and athlete preparation for the strategic and tactical decision-making process essential for success in short-track.